2022
DOI: 10.4097/kja.22279
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Block in Children: a Narrative Review

Abstract: This article has been accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination, and proofreading processes, which may lead to differences between this version and the version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 81 publications
(128 reference statements)
0
14
0
Order By: Relevance
“…The pediatric publications are in line with the adult literature. Two recent reviews, one meta‐analysis, and one narrative review, conclude that the evidence base for ESPB in children is still suboptimal and largely inconclusive 42,43 . As in adults, it appears to be of some use in less invasive surgical procedures but not for more major surgery (e.g., video‐assisted thoracic surgery vs. posterolateral thoracotomy and pectus excavatum repair) 44,45 .…”
Section: Pediatric Fascial Plane Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…The pediatric publications are in line with the adult literature. Two recent reviews, one meta‐analysis, and one narrative review, conclude that the evidence base for ESPB in children is still suboptimal and largely inconclusive 42,43 . As in adults, it appears to be of some use in less invasive surgical procedures but not for more major surgery (e.g., video‐assisted thoracic surgery vs. posterolateral thoracotomy and pectus excavatum repair) 44,45 .…”
Section: Pediatric Fascial Plane Blocksmentioning
confidence: 99%
“…Two recent reviews, one meta-analysis, and one narrative review, conclude that the evidence base for ESPB in children is still suboptimal and largely inconclusive. 42,43 As in adults, it appears to be of some use in less invasive surgical procedures but not for more major surgery (e.g., video-assisted thoracic surgery vs. posterolateral thoracotomy and pectus excavatum repair). 44,45 It also provides additional analgesic effects when compared to no block or sham block 46,47 but is not beneficial when compared to other established regional anesthetic techniques.…”
Section: Erector Spinae Plane Block (Espb)mentioning
confidence: 99%
“…In 2017, Chin et al [ 47 ] reported a successful perioperative pain management using ESP block in a pediatric patient who underwent oncological thoracic surgery. Since then, the ESP block has been applied in a wide range of pediatric clinical scenarios [ 48 ].…”
Section: Fascial Plane Blocks For Cardiac Surgerymentioning
confidence: 99%
“…The thoracic paravertebral block is an alternative technique to epidural catheter in these patients. Furthermore, new methods of regional analgesia, such as intercostal nerve block and erector spinae plane block, are also applied as part of multimodal analgesia regimens [13][14][15].…”
Section: Introductionmentioning
confidence: 99%